The SARS-CoV-2 receptor ACE2 is expressed in mouse pericytes but not endothelial cells: Implications for COVID-19 vascular research - Muhl, Lars; He, Liqun; Sun, Ying; Andaloussi Mäe, Maarja; Pietilä, Riikka; Liu, Jianping; Genové, Guillem; Zhang, Lei; Xie, Yuan; Leptidis, Stefanos; Mocci, Giuseppe; Stritt, Simon; et al. (Stem cell reports, 2022)
Humanized mouse models and mouse-adapted SARS-CoV-2 virus are increasingly used to study COVID-19 pathogenesis, so it is important to learn where the SARS-CoV-2 receptor ACE2 is expressed. Here we mapped ACE2 expression during mouse postnatal development and in adulthood. Pericytes in the CNS, heart, and pancreas express ACE2 strongly, as do perineurial and adrenal fibroblasts, whereas endothelial cells do not at any location analyzed. In a number of other organs, pericytes do not express ACE2, including in the lung where ACE2 instead is expressed in bronchial epithelium and alveolar type II cells. The onset of ACE2 expression is organ specific: in bronchial epithelium already at birth, in brain pericytes before, and in heart pericytes after postnatal day 10.5. Establishing the vascular localization of ACE2 expression is central to correctly interpret data from modeling COVID-19 in the mouse and may shed light on the cause of vascular COVID-19 complications. •Detailed Ace2/ACE2 expression patterns are reported for multiple mouse organs•Vascular Ace2/ACE2 expression occurs in pericytes but not endothelial cells•Ace2/ACE2 expression is organotypic and developmentally regulated•Ace2/ACE2 expression in pericytes may suggest their involvement in COVID-19 Through application of scRNA-seq and tissue imaging, we provide a detailed mapping of the expression of Ace2, the mouse ortholog of human ACE2/SARS-CoV-2 receptor. We demonstrate prominent but organotypic expression of Ace2 in certain pericytes, fibroblasts, and epithelial cells, but not in any investigated type of endothelial cells. Knowledge about Ace2 expression is important for COVID-19 modeling in mouse.